Prevalência e fatores associados à insônia em estudantes de educação física durante o ensino remoto na Universidade Pública do Norte do Tocantins - Machado, Paloma da Silva (Universidade Federal do Tocantins, 2023)
The Pandemic hit many countries in 2020, including Brazil, which joined numerous measures to combat the spread of the virus, interfering in the life of society, with the requirement of social isolation and that the recommendation "stay at home" adopted to stop the spread of the virus. COVID-19 has affected higher education, bringing university students significant changes, from an economic point of view, in physical, mental, emotional, social, spiritual, environmental, political aspects and negative effects on the quality and quantity of sleep and, consequently, the installation of disorders. Of sleep, especially insomnia. In view of this, the present study aims to estimate the prevalence and factors associated with insomnia in Physical Education students during remote teaching at the Universidade Pública do Norte do Tocantins. This is a descriptive, cross-sectional study with a quantitative approach, adopting a non-probabilistic sample which took place online due to the pandemic scenario, and the mandatory social distancing as a way of preventing COVID-19. Data were collected through online forms through Google Forms and sent to each participant individually through their institutional email. Sociodemographic data were collected and the Insomnia Severity Index (ISI) was applied. This research was submitted and approved by the Ethics and Research Committee of the State University of Tocantins through opinion no 5.117.581 and CAAE 52981121.7.0000.8023. Data were analyzed using the Statistical Package for Social Sciences 22.0 software and participants were divided into two groups: with insomnia and without insomnia according to the ISI. The sample consisted of 68 Physical Education students aged between 18 and 45 years. 55.9% (n=38) were female and 40.1% (n=30) were male. Among these, 51.5% (n=35) have some degree of insomnia severity and 48.5% (n=33) do not have insomnia. The degree of insomnia severity was more prevalent in females, with 42.1% (n=16) mild insomnia and 18.4% (n=7) moderate insomnia. Marital status (p=0.05) and religion (p=0.02) showed a significant difference between the two groups. The presence of insomnia in students of the Physical Education Course was high, especially among females. Therefore, it is extremely important to evaluate and analyze sleep disorders in the educational context, aiming at the search for the promotion and prevention of students' health.